-7(x+3)=3(-5-2x)

Simple and best practice solution for -7(x+3)=3(-5-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+3)=3(-5-2x) equation:


Simplifying
-7(x + 3) = 3(-5 + -2x)

Reorder the terms:
-7(3 + x) = 3(-5 + -2x)
(3 * -7 + x * -7) = 3(-5 + -2x)
(-21 + -7x) = 3(-5 + -2x)
-21 + -7x = (-5 * 3 + -2x * 3)
-21 + -7x = (-15 + -6x)

Solving
-21 + -7x = -15 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-21 + -7x + 6x = -15 + -6x + 6x

Combine like terms: -7x + 6x = -1x
-21 + -1x = -15 + -6x + 6x

Combine like terms: -6x + 6x = 0
-21 + -1x = -15 + 0
-21 + -1x = -15

Add '21' to each side of the equation.
-21 + 21 + -1x = -15 + 21

Combine like terms: -21 + 21 = 0
0 + -1x = -15 + 21
-1x = -15 + 21

Combine like terms: -15 + 21 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x | | X-4y=3b | | 3(x-1)=2x-3+3 | | 8w=9+9w | | 6x^2-10x-7=0 | | (x/4)+8=-8 | | X=10x-12 | | Y^2-y+.25=0 | | 5=8m+4-7 | | 37-2x=6+7(-3x-1) | | -5+5m=-10+4m |

Equations solver categories